The electronic states of ITO–MoS2: Experiment and theory - López Galan, Óscar; Ramos Murillo, Manuel Antonio; Nogan, John; Ávila-García, Alejandro; Boll, Torben; Heilmaier, Martin (2021)
We report a combination of experimental results with density functional theory (DFT) calculations to understand electronic structure of indium tin oxide and molybdenum disulfide (ITO–MoS2) interface. Our results indicate ITO and MoS2 conform an n-type Schottky barrier of c.a. − 1.0 eV due to orbital interactions; formation of an ohmic contact is caused by semiconducting and metal behavior of ITO as a function of crystal plane orientation. ITO introduces energy levels around the Fermi level in all interface models in the Γ-Μ-Κ-Γ path. The resulted Van der Waals interface and the values of Schottky barrier height enhance electron carrier injection.